First Step Next: A Best-Evidence Synthesis of Replication Randomized Controlled Trials From 2009 to 2021. (February 2023) - Frey, Andy J.; Small, Jason W.; Walker, Hill M.; Mitchell, Brandon; Seeley, John R.; Feil, Edward G.; Lee, Jon; Forness, Steven R.
Early intervention efforts have been effective in reducing disruptive behaviors and the probability of poor developmental outcomes. Early interventions include common practice elements to improve social functioning and decrease problem behaviors that disrupt the teaching-learning process. The First Step Next intervention has been well validated across early childhood and early elementary settings. In the present article, we provide a best-evidence synthesis of five randomized controlled replication studies between 2009 and 2021. Collectively, these studies show the intervention has resulted in small to large effect sizes and statistically significant improvements, compared with students randomized to control conditions, on multiple indicators of prosocial and problem behavior. The current synthesis focuses on a range of outcomes across elementary and preschool populations, as well as implementation fidelity and social validity ratings, to help school professionals in determining whether First Step Next might be useful in their efforts to support students at risk of school failure.